Regulatory Approval With Real-World Data From Regulatory Science Perspective in Japan - Maeda, Hideki; Ng, Daniel Bin (Frontiers in Medicine, 2022)
Recently, there has been a growing trend in clinical development to utilize real-world data (RWD) to improve the efficiency of drug/medical device development. Especially, the use of RWD to generate real-world evidence (RWE) in regulatory approval is currently undergoing a period of great change with an increasing degree of active discussion. In Japan, RWE has been used in the control arms of clinical trials, observational studies, post-marketing surveillance, and public knowledge-based applications for regulatory approval. In this paper, we summarize the history and the current situation of RWE and focus on its utilization for the purpose of regulatory approval. In addition, we will discuss the issues and perspectives for registry research in the utilization for regulatory approval in Japan.